Organic acids component of Tempoyak - Neti Yuliana (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
This study was mainly conducted to identify the of organic acids component of tempoyak. Acidity and pH changes during fermentation process of fermented tempoyak were also evaluated. The results revealed that there were significant changes in pH ranging from 7 to 4 and acidity (6 mg/g- 38 mg/g) attributed to organic acids present in tempoyak. These organic acids were malic acid (145,9 mg/ml), followed by lactic acid (34,1 mg/ml), and small amount of acetic acid (14,2mg/ml). Key words: Tempoyak; organic acids; pH and acidity